The relationship between parental screen guilt and subjective well-being in mothers - Saula Rahmadianti Krisma Pertiwi; Fransisca Iriani Roesmala Dewi (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study aims to examine the relationship between Parental Screen Guilt (PSG) and Subjective Well-Being (SWB) among mothers with children under 18 years old. PSG refers to the guilt parents feel when they perceive their children’s screen use as inconsistent with ideal parenting standards. SWB was assessed through two affective components: Positive Affect (PA) and Negative Affect (NA). This research employed a quantitative correlational design, involving 171 mothers recruited through purposive sampling. The instruments used were the 5-item PSG scale adapted from Wolfers et al. (2024) and the I-PANAS-SF to measure PA and NA. The findings show that PSG is positively associated with both PA and NA, indicating that higher levels of guilt are linked to a greater tendency to experience both positive and negative affect in daily life. These results highlight that guilt in digital parenting elicits multifaceted emotional responses, where PSG operates as a dual-function psychological mechanism that may generate emotional discomfort while simultaneously promoting awareness and self-correction. Furthermore, guilt is shaped not only by the child’s screen time duration but also by the discrepancy between ideal digital parenting standards and everyday screen-use practices. Thus, PSG can be understood as a form of dissonance between parental values and the realities of real-life parenting. Overall, this study enriches the theoretical understanding of moral emotions in digital parenting and offers practical implications for developing educational programs and interventions to help parents manage guilt in healthier, more constructive ways.